2013
DOI: 10.5588/ijtld.12.0654
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis stigma in Gezira State, Sudan: a case-control study

Abstract: Although TB stigma among the Gezira population was found to be mild, it can affect treatment adherence. Empowering both TB patients and communities by increasing their knowledge through proper education programmes could effectively contribute to the effort of controlling TB in the state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 0 publications
0
19
2
11
Order By: Relevance
“…In Zambia and Sudan, observational studies of TB patients reported gender, age, education, geographical location, employment, and TB awareness to be associated with TB stigma [39,53]. Among TB patients in our study, knowing the correct causes of TB, knowledge of the role of TB in HIV, perceived HIV stigma and race/ ethnic group were associated with TB stigma.…”
Section: Discussionmentioning
confidence: 45%
“…In Zambia and Sudan, observational studies of TB patients reported gender, age, education, geographical location, employment, and TB awareness to be associated with TB stigma [39,53]. Among TB patients in our study, knowing the correct causes of TB, knowledge of the role of TB in HIV, perceived HIV stigma and race/ ethnic group were associated with TB stigma.…”
Section: Discussionmentioning
confidence: 45%
“…The finding that one third of the patients would not tell anybody about their illness, might suggest that fear of social exclusion still exists (Story et al 2006 ) and necessitates further research on stigma in TB (Ahmed Suleiman et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 Delays in TB case detection and treatment are associated with lack of TB knowledge, poor attitudes toward personal health, traditional beliefs and cultural factors, inability to access affordable healthcare services, and fear of stigmatization. 4 – 9 …”
Section: Introductionmentioning
confidence: 99%